Professionnalisation des métiers de l'enseignement : l'apport de l'observation des pratiques - Joël Clanet (Nantes Université, 2010)
The professionalization of the teaching profession, a special moment in teachers' professional development, is not at this point being envisaged with reference to the practices related to teaching subjects. And these professional practices themselves have little reference to what actually occurs in the classroom during teaching-learning situations. This article addresses the contributions to our knowledge of teaching practices in context made by several studies, many of which were conducted by teams affiliated with the OPEN (Observation des Pratiques Enseignantes) network. The observation of teachers' activity in the classroom and an understanding of the logic underlying these activities should help to better define the organizing processes in situation. Whether it be the choice of task, time management, or the management of classroom interactions, a better understanding of the organizing processes at work in the observed situations is not only of heuristic interest, but it can also enrich the reflexive practices of the teacher-practitioners. Teachers, who are increasingly viewed as reflexive practitioners, have much to gain by enriching their referents for the analysis of those elements that enhance their pedagogical functioning, in the sense of a reflection on action in order to act.